Implementation of bureaucratic reforms to support public services for disabled groups in Central Java - Saputra, Andreas Vishnu (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Background: This research aims to conduct a study of the implementation of bureaucratic reform related to public services, especially the disability group. Bureaucratic reform is aimed at making changes both in terms of institutional aspects, governance, human resources and legal regulations to realize a bureaucratic agenda that improves the welfare of the disabled community. One of the agendas for implementing bureaucratic reform is to improve the quality of public services. Public services for people with disabilities are one manifestation of state services to meet their needs which have been neglected. Currently, the quality of public services is felt to be unsatisfactory with many complaints about the quality of public services provided by local governments and institutional ministries for people with disabilities. Improving the quality of public services is carried out by synchronizing various aspects by improving the quality of implementing apparatus and forming adaptive organizations so that they can produce innovation to anticipate developments in the needs of marginalized groups. Methods: The method used in this research is to conduct a literature review and analyze secondary data, both quantitative and qualitative, obtained from previous research or from documentation or publications. Findings: From the results of the analysis, it is found that implementing bureaucratic reform is the best way to improve the quality of public services which can not only serve current conditions but can also adapt to developmental needs which results in public service innovation. Conclusion: This research also found that the quality received by disability groups was still low. Novelty/Originality of this Study: Its examination of bureaucratic reforms specifically aimed at enhancing public services for disabled groups in Central Java uniquely addresses the intersection of governance, institutional changes, and the specific needs of marginalized groups. Additionally, it emphasizes adaptive organizations and service innovation to improve accessibility and inclusivity.